On the Symbol-Pair Distance of Repeated-Root Constacyclic Codes of Prime Power Lengths* - Dinh H. (2017)
IEEE Let p be a prime, and & #x03BB; be a nonzero element of the finite field Fpm. The & #x03BB;-constacyclic codes of length ps over Fpm are linearly ordered under set-theoretic inclusion, i.e., they are the ideals & #x027E8;(x & #x2212; & #x03BB;0)i & #x027E9;, 0 & #x2264; i & #x2264; ps of the chain ring Fpm & #x005B;x & #x005D; / & #x027E8;xps & #x2212; & #x03BB; & #x027E9;. This structure is used to establish the symbol-pair distances of all such & #x03BB;-constacyclic codes. Among others, all MDS symbol-pair constacyclic codes of length ps are obtained.